Establishing a Virtual Clinic for Developmental Dysplasia of the Hip: A Prospective Study. Issue 4 (22nd April 2021) - Murphy, Evelyn P.; Fenelon, Christopher; Kennedy, Jim F.; O'Sullivan, Michael D.; Noel, Jacques; Kelly, Paula M.; Moore, David P.; O'Toole, Patrick J.
Abstract : Background: The aim was to describe the introduction and operation of a virtual developmental dysplasia of the hip (DDH) clinic. Our secondary objectives were to provide an overview of DDH referral reasons, treatment outcomes, and adverse events associated with it. Methods: A prospective observational study involving all patients referred to the virtual DDH clinic was conducted. The clinic consultant delivered with 2 DDH clinical nurse specialists (CNS). The outcomes following virtual review include further virtual review, CNS review, consultant review or discharge. Treatment options include surveillance, brace therapy, or surgery. Efficiency and cost analysis were assessed. Results: Over the 3.5-year study period, 1002 patients were reviewed, of which 743 (74.2%) were female. The median age at time of referral was 7 months, (interquartile range of 5 to 11) with a median time to treatment decision of 9 days. Median waiting times from referral to treatment decision was reduced by over 70%. There were 639 virtual reviews, 186 CNS reviews, and 144 consultant reviews. The direct discharge rate was 24%. One hundred one patients (10%) had dislocated or subluxed hips at initial visit while 26.3% had radiographically normal hips. Over the study period 704 face to face (F2F) visits were avoided. Cost reductions of €170 were achieved per patient, with €588, 804 achieved in total. Eighteen parents (1.8%) opted for F2F instead of virtual review. There were no unscheduled rereferrals or recorded adverse events. Conclusion: We report the outcomes of the first prospective virtual DDH clinic. This clinic has demonstrated efficiency and cost-effectiveness, without reported adverse outcomes to date. It is an option to provide consultant delivered DDH care, while reducing F2F consults. Level of Evidence: Level III.